Strategi Penjualan Produk Olahan Singkong (Sampeuin) di Pandemi Covid-19 di Kabupaten Karawang - Dedi Rianto Rahadi; Hani Tri Lestari; Desita Maharani (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
Indonesia experienced a drastic economic downturn during the COVID-19 pandemic. The Micro, Small and Medium Enterprises (MSME) sector is the economic sector that is affected. Researchers analyzed from SWOT on the marketing of Sampeuin cassava processed products and determined marketing strategies for Sampeuin cassava processed products in the Covid-19 pandemic. This research was conducted on cassava processing SMEs. In this study, researchers used qualitative research methods. Based on the analysis of the "Sampeuin" cassava processing business using a SWOT (Strength, Weakness, Opportunity, Threat) analysis, there is a use of cassava as a processed food ingredient. Cassava which has many benefits for the human body is processed into "Sampeuin" which is used as a business opportunity in the snack food sector. Since the advent of social media, many business owners have used social media to do business.